1992
DOI: 10.1038/sj.bdj.4807776
|View full text |Cite
|
Sign up to set email alerts
|

The clinical performance of a glass polyalkenoate (glass ionomer) cement used in a 'sandwich' technique with a composite resin to restore Class II cavities

Abstract: The use of glass polyalkenoate (GPA) cement in conjunction with composite resin using an acid etch technique is now well known and a 'sandwich' of tooth/GPA cement/composite resin has been recommended to form the cervical seal at the base of approximal boxes in Class II cavities. This paper reports on the 2-year results of a controlled clinical trial using a commercial GPA lining cement. The trial was designed to evaluate the efficacy of this 'sandwich' technique. Sixty-four restorations in the mouths of 22 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Improved marginal adaptation was observed initially but also a high clinical failure rate due to continuous loss of the GIC. 10,12 Kemp-Scholte and Davidson showed that materials with lower elasticity modulus can act as an elastic buffer, which relieved contraction stresses and improved marginal integrity. 25 Since PMRC include resins with a modulus of elasticity value between those of RC and GIC, the material may work as a stress breaking barrier between the tooth and the composite.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Improved marginal adaptation was observed initially but also a high clinical failure rate due to continuous loss of the GIC. 10,12 Kemp-Scholte and Davidson showed that materials with lower elasticity modulus can act as an elastic buffer, which relieved contraction stresses and improved marginal integrity. 25 Since PMRC include resins with a modulus of elasticity value between those of RC and GIC, the material may work as a stress breaking barrier between the tooth and the composite.…”
Section: Discussionmentioning
confidence: 97%
“…The open sandwich technique was preferably recommended in high-caries-risk patients because of the fluoride release from the material. 10,11 The GIC covered most of the exposed dentin and extended to the periphery of the proximal box to form the cervical seal. Clinical failure rates of this technique have been reported between 13 and 35% after 2 years and 75% after 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…The 'cervical lining' technique (also known as the 'open sandwich', a term not favoured by the first author) was described in 1984, 7 and clinical trials are supporting its usefulness, provided that an appropriate GIC is used. [77][78][79][80] Glassionomer cements can be effective fissure sealants and are useful when optimum moisture control for resinbased sealants cannot be achieved. 81 Although clinical retention appears less than for resin-based sealants, prevention of fissure caries is comparable.…”
Section: Types I and Ii Glass-ionomer Cementsmentioning
confidence: 99%
“…The original sandwich concept, with the GIC cement element open to the oral environment, has been recommended in high‐caries‐risk patients 20 . Several studies in adult population showed clinical failure rates between 13% and 35% after 2 years, and 75% after 6 years 21–23 . To increase the quality and longevity of the open‐sandwich restoration, a modified open‐sandwich restoration was suggested 24 .…”
Section: Introductionmentioning
confidence: 99%